Asas Retroaktif pada Kasus Pelanggaran HAM (Perspektif Hukum Islam) - Ikhwan Ikhwan (Ulumuna, 2009)
The principle of retroactiveness in The Act, Number 26 in 2000 on Human Rights Jurisdiction provokes pros and cons. In one hand, severe violence against human rights is an extra ordinary crime that requires special treatment. On the other hand, retroactive legislation is against the principle of legality. In Islamic law, an act is considered a crime if it is proven by juridical evidences. An act is not considered a crime unless there is punishment for it. Therefore, every juridical decision adheres to the principle of legality that limits the extent of a law just for the future, not retroactive. According to most Muslim scholars, the principle of retroactiveness could be implemented if a new law is more just and humane without breaking the attainment of law ends. Implementation of the principle for severe violence against human rights is not allowed because it does not meet such requirement.